The influence of annealing on a large specific surface area and enhancing electrochemical properties of reduced graphene oxide to improve the performance of the active electrode of supercapacitor devices - Karaphun, Attaphol; Phrompet, Chaiwat; Tuichai, Wattana; Chanlek, Narong; Sriwong, Chaval; Ruttanapun, Chesta (My University, 2021)
Influence of annealing process on microstructure, large specific surface area and enhancing electrochemical properties to synthesize reduced graphene oxide (rGO) for the supercapacitor electrode was investigated. Thermal annealing process of rGO (rGO_An) was improved crystallinity and electrical conductivity. BET analysis of rGO_An sample exhibited the occurrence of large mesoporous and macrospores with a huge specific surface area of 672.1 m2/g and an average pore size of 46.2 nm, resulting the rGO_An sample activates more electrodes than rGO sample. Specific capacitance (Cs) was affected by improving conductivity through annealing process with an excellent cycling stability after 750 cycles for GCD tests of 97.32%, which exhibited the highest value and an average energy density of 412.096 F g−1 and 74.5 Wh kg−1, respectively at 1 A g−1. Thus, annealing process can occur with large mesoporous and macrospores pore improving the electrical conductivity and stability to be applied as an electrode in supercapacitor.
Keywords: Annealing process; Electrochemical properties; Reduced graphene oxide (rGO) microstructure; Supercapacitor devices